Manivesting Law Off Attraction Dalam Menata Masa Depan Mahasiswa Fresh Graduate - sinta, Sinta; Surawan (STAI Terpadu Yogyakarta, 2025)
Manifesting law off attraction is the law of attraction in the mind, what we think is a reflection of the tremendous force that is going to happen, if we think about it will send a signal that is realized in the real world. These goals or targets will increase mental thinking because the goals or targets that are thought of will motivate a person to behave and act, especially if he is confident that these goals and objectives will be achieved. The many tasks that accumulate, the competition of the modern era and the problems of life that plague fresh graduate students can they always think positively even with complicated circumstances, because at that age they really start life to work, prepare themselves to ease the burden on their parents, and some even think about building a household. This type of research is qualitative with a descriptive approach, which produces descriptive data in the form of words or sentences that are written systematically. The data collection technique was through interviews and documentation with students who had graduated from college, with a total of 10 male and 12 female students. The data analysis technique with interactive analysis focuses on extracting the meaning of the words and sentences used by the respondents during the interview. In conclusion, most new graduates always think positively in order to complete their studies. In fact, positive thoughts always make them very confident that they will get a good job and live a good life